Influence of the British colonialists on waqf practice in Penang, Malaysia: reflections on its legal history - Mohamad, Nor Asiah; M Dahlan, Salehudin; M Dahlan, Nuarrual Hilal (UUM, 2022)
Previous researchers’ general impression inferred that western colonialists contributed to the decline of waqf practice in the Muslim world. However, whether this statement is accurate in the case of the British colonial rule in Penang is uncertain. This research paper reviewed waqf practice in Penang under the British colonial rule. This paper also discussed how the colonial rule influenced and impacted waqf development in the state. Due to the nature of the study, doctrinal legal research methodology was employed, which involved examining law cases, legal provisions, policy documents, books, journal articles, and working papers. This study found that the British colonialists did not abolish waqf but improved its practice according to English trust and charitable laws. Unlike other colonialists, waqf practice under British rule in Penang had flourished, albeit with some flaws. The authors are convinced that this writing will provide a balanced perception of the colonialists and their hidden purpose in occupying the Malay states.